PENGARUH REAKSI AFEKTIF DAN KOGNITIF DALAM LIVE STREAMING COMMERCE TERHADAP PERILAKU IMPULSIVE BUYING PADA MAHASISWA PENDIDIKAN EKONOMI - Melanie, Melanie; Aisyah, Iis; Roro Suci Nurdianti, Raden (COSMOS : Jurnal Ilmu Pendidikan, Ekonomi dan Teknologi, 2024)
The problem in the research is that students cannot control their desire to buy products in live streaming commerce and take action spontaneously, resulting in impulsive buying behavior. This research also aims to determine the influence of affective and cognitive reactions in live streaming commerce on impulsive buying behavior. This research uses a quantitative survey type method with an explanatory research design. The population in this study were economic education students from the Class of 2022 and 2023 using a proportionate stratified random sampling technique, totaling 164 students. The collection technique uses a questionnaire and the data analysis technique uses SPSS version 25.0 for Windows. The research results show that: 1) There is a partially significant positive influence (significance value of 0.000 or calculated t value of 6.414) on the affective reaction variable which is related to impulsive buying behavior; 2) There is a partially significant positive influence (significance value of 0.000 or calculated t value of 4.657) on the cognitive reaction variable related to impulsive buying behavior; and 3) There is a joint significant influence (significance value of 0.000 or calculated f value of 57.344) between affective and cognitive reactions to the variable measuring impulsive buying behavior. The findings of this study also show that 41.6% of the reasons behind impulse buying behavior can be predicted by combining affective and cognitive reactions.